K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

5 tháng 2 2016

N = x - 34 - [(15 + x) - (23 - x)]

= x - 34 - (15 + x - 23 + x)

= x - 34 - (2x - 8)

= x - 34 - 2x + 8

= -x - 26

30 tháng 5 2017

34*56+34+43+34

=34*(56+43+1)

=34*100

=3400

15*23+15+53+15*23+15

=15*(23+53+23+1)

=15*100

=1500

30 tháng 5 2017

a, 34 x 56 + 34 x 43 + 34

= 34 x ( 56 + 43 + 1 )

= 34 x 100

= 3400

b, 15 x 23 + 15 + 53 + 15 x 23 + 15

= 15 x ( 23 + 53 + 23 + 1 )

= 15 x 100

= 1500

21 tháng 8 2018

a ) x ∈ ± 23 28 . b ) x ∈ − 23 6 ; 35 6 . c ) x ∈ − 17 60 ; 97 60 . d ) x ∈ 67 140 ; 143 140 .

14 tháng 1 2017

a/ M = (71+x)-(-24+x)+(-35-x) = 71 + x + 24 - x - 35 - x = (71 + 24 - 35) - x = 95 - 35 - x = 60 - x

b/ N=x-34-[(15+x)-(23-x)] = x - 34 - (15 + x - 23 + x) = x - 34 - (-8 + 2x) = x - 34 + 8 - 2x = -26 - x

14 tháng 1 2017

\(a,M=\left(71+x\right)-\left(-24+x\right)+\left(-35-x\right)\)

        \(=71+x+24-x-35-x\)

        \(=60-x\)

\(b,N=x-34-\left[\left(15+x\right)-\left(23-x\right)\right]\)

       \(=x-34-\left(15+x-23+x\right)\)

       \(=x-34-15-x+23-x\)

       \(=-26-x\)

12 tháng 1 2016

x-34-[(15+x)-(23-x)]=15-21

x-34-[(15+x)-(23-x)]= -6

x-34-15-x-23+x      = -6

(x-x+x) + (-34-15-23)= -6

    x     + -72           = -6

   x                        = -6-(-72)

   x                        =66   

13 tháng 12 2019

a)  x − 2 3 = − − 1 5 + 3 4 ⇔ x − 2 3 = − 1 5 + 3 4 = 11 20 ⇔ x − 2 3 = 11 20 x − 2 3 = − 11 20 ⇔ x = 73 60 x = 7 60

b)  x − 3 = 1 5 + 1 7 − 1 14 ⇔ x − 3 = 1 5 + 1 14 = 19 70 ⇔ x − 3 = 19 70 x − 3 = − 19 70 ⇔ x = 229 70 x = 191 70

20 tháng 12 2019

Đáp án cần chọn là: D

10 tháng 5 2022

23/34 x17/15 x5/16

= 23/30 x5/46

= 1/12

`23/34 xx 17/15 xx5/46`

`= 23/30 xx 5/46`

`= 1/12`

18 tháng 1 2018

(x-15) - (x-3) = -(x+17) - 1 <=> x-15-x+3 = -x-17-1 <=> x = -6

-(x-12) - (x-5) = -(4-x) + 13 <=> -x+12-x+5 = -4+x+13 <=> -3x = -8 => x = 8/3

34 - (x-7) = x+15 - (x+23) <=> 34-x+7 = x+15-x-23 <=> -x = -49 <=> x = 49

25 tháng 1 2017

mk chỉ làm ý A thui nha

\(A=\left(71+x\right)-\left(-24-x\right)+\left(-35-x\right)\)

\(A=71+x+24+x+\left(-35\right)-x\)

\(A=\left[71+24+\left(-35\right)\right]+\left(x+x-x\right)\)

\(A=60+x\)

Vậy \(A=60+x\)

25 tháng 1 2017

\(a,A=\left(71+x\right)-\left(-24-x\right)+\left(-35-x\right)\)

       \(=71+x+24+x-35-x\)

       \(=60+x\)

\(b,B=x-34-\left[\left(15+x\right)-\left(23-x\right)\right]\)

       \(=x-34-\left(15+x-23+x\right)\)

       \(=x-34-15-x+23-x\)

       \(=-x-26\)